2014
DOI: 10.1038/ejcn.2014.253
|View full text |Cite
|
Sign up to set email alerts
|

Iodine deficiency in pregnant women in Austria

Abstract: This study shows that pregnant women in the Vienna area have a potentially clinically significant iodine deficiency and that currently recommended doses of iodine supplementation may not be sufficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
33
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 35 publications
9
33
1
2
Order By: Relevance
“…Additionally, this study further supports the notion that SAC median UIC could be an imprecise approach for estimating iodine status in pregnant women [7][8][9][10][11]. In consolidation, The IGN has revealed that 29 countries reported iodine deficiency in pregnant women, whereas their SAC populations were sufficient [46].…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Additionally, this study further supports the notion that SAC median UIC could be an imprecise approach for estimating iodine status in pregnant women [7][8][9][10][11]. In consolidation, The IGN has revealed that 29 countries reported iodine deficiency in pregnant women, whereas their SAC populations were sufficient [46].…”
Section: Discussionsupporting
confidence: 79%
“…The most recent UNICEF guidelines have likewise stated that measuring UIC in SAC may conceal suboptimal iodine intake in subsets of vulnerable groups, including pregnant women [17]. Studies from Austria [7], Denmark [9], China [11] and the United States [47] have also demonstrated marked iodine insufficiency among pregnant women despite using iodised salt and/or iodine supplements. Taken together, our study and the prior reports advocate that the health authorities in each country should consider measuring iodine intake in pregnant women independently from SAC to accurately evaluate iodine adequacy in this vulnerable group [7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Iodine deficiency during pregnancy also significantly increase the risk of delayed neurodevelopment and poor cognitive functions in the offspring [3,4]. Although many countries have implemented the universal salt iodisation (USI) policy to ensure adequate access to iodine by the general public [5,6], numerous reports from different developed and developing countries have demonstrated high rates of iodine insufficiency among pregnant women [7][8][9][10][11]. Accordingly, many researchers have emphasised the need for alternative means (e.g.…”
Section: Introductionmentioning
confidence: 99%